Evaluation of some newly introduced pomegranate (Punica granatum) genotypes under mid-hills conditions of Himachal Pradesh - SUPARNA SINHA (The Indian Journal of Agricultural Sciences, 2016)
Twenty pomegranate (Punica granatum L.) genotypes namely Parfyanets, Saharnyi, Loulou, Nusai, Cloud, Green Globe, Podarok, Crab, Al-sirin-nar, Purple Heart, Kaim-anar, 20090265, Gulyalek, Haku-botan, Alk Pust Ghermez Saveh, Eve, Dewey, Ovadan, Sogdiana and Orange were evaluated under mid hills conditions of Himachal Pradesh. Largest and heaviest fruits were observed in Green Globe (296.3 g), whereas lightest fruits were in 20090265 (144.56 g). Aril percentage varied from 47.95% to 70.94% while as maximum aril/rind ratio was recorded in 20090265 (2.55) and minimum in Purple Heart (1.12). TSS content was maximum (15.87Â°B) in Purple Heart and minimum (9.93Â°B) in Ovadan. Titratable acidity varied from 2.26% to 0.66%. Wide variability in terms of total sugar content were also observed which ranges from 7.55% (Ovadan) to 14.13% (Purple Heart). Genotype Ovadan (30.60 mg/100 ml) have highest anthocyanins content whereas Hakubotan (3.23 mg/100 ml) have lowest anthocyanin content. Maximum phenols from the juice was obtained in Al-sirin-nar (981.24 mg/100 g), whereas it is minimum in Alk Pust Ghermez Saveh (308.03 mg/100 ml). Dewey, Green Globe, Podarok and Loulou are most suitable for use as a cultivars directly being big size of fruit, medium to soft seeded and high yield potential or in used for future breeding programme for further improvement in local cultivars.